2010
DOI: 10.1371/journal.pone.0014367
|View full text |Cite
|
Sign up to set email alerts
|

Adolescence As Risk Factor for Adverse Pregnancy Outcome in Central Africa – A Cross-Sectional Study

Abstract: BackgroundSub-Saharan Africa has the highest rates of maternal and neonatal mortality worldwide. Young maternal age at delivery has been proposed as risk factor for adverse pregnancy outcome, yet there is insufficient data from Sub-Saharan Africa. The present study aimed to investigate the influence of maternal adolescence on pregnancy outcomes in the Central African country Gabon.Methodology and Principal FindingsData on maternal age, parity, birth weight, gestational age, maternal Plasmodium falciparum infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
65
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 17 publications
26
65
2
4
Order By: Relevance
“…Again, for Kurth et al, when performing fewer antenatal care consultations compared to adult mothers adolescents were at risk of having babies with a small birth weight (3.3±1.9 against 4.4±1.9 on average; P <0.01). 10 Our study showed a 6 folds increased risk of low birth weight in the poor outcome group. Bulkumez et al emphasized on the need of sufficient antenatal care consultations which reduces the occurrence of poor outcome.…”
Section: Discussionsupporting
confidence: 45%
“…Again, for Kurth et al, when performing fewer antenatal care consultations compared to adult mothers adolescents were at risk of having babies with a small birth weight (3.3±1.9 against 4.4±1.9 on average; P <0.01). 10 Our study showed a 6 folds increased risk of low birth weight in the poor outcome group. Bulkumez et al emphasized on the need of sufficient antenatal care consultations which reduces the occurrence of poor outcome.…”
Section: Discussionsupporting
confidence: 45%
“…Inadequate number of antenatal visits has often been cited as deleterious factor of fetal outcome [12,39]. However, a free provision of quality health care including antenatal package was provided throughout the duration of the PREGACT trial.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, delivery before 32 weeks was higher in early teenage women (10.0 vs. 6.9 %), but this difference did not reach a significant level (P = 0.62). The risk of preterm delivery is 1.9 times more among teenagers [12,13]. There are no significant differences in birth weights between the two groups; this is due to similar prevalence of preterm delivery 32-36 weeks and very preterm delivery \32 weeks, PROM, PIH and PET which adversely affect birth weights.…”
Section: Discussionmentioning
confidence: 99%